The Mines Rescue Service in the Polish System of Crisis Management - Tomasz Ciupa (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The paper presents the place of the mines rescue service in the structures of the crisis management system in Poland. The mines rescue service as one of several entities of the rescue system in Poland focuses on helping injured miners and other people trapped underground. The paper mentions existing legal regulations concerning the mines rescue service and other emergency services. An important piece of legislation for members of mines rescue teams, is the ordinance of the Minister of Energy of 16 March 2017 which introduces a number of revolutionary changes such as obligation to deliver qualified first aid and on-the-spot psychological support. In this way the mines rescue service has become more utilitarian and more universal and therefore may be efficiently used for operations in more general crisis situations and even better contribute to the smooth functioning of the state.